Using a logic model to evaluate a novel video-based professional development activity for general practice clinical educators. Issue 2 (15th March 2023) - Clement, Tim; Howard, Duncan; Lyon, Eldon; Molloy, Elizabeth
ABSTRACT: The teaching and learning that takes place in clinical settings has a significant influence on the practice of future health professionals. This article describes the use of a logic model and case study methodology to evaluate an online and face-to-face video-club, a novel professional development activity designed with the aim of improving clinical educators' teaching practice. A video-club brings together a small group of clinical educators who have a shared interest in exploring their educator role through collective inquiry, using video-recordings of their authentic teaching practices as stimuli for learning discussions. The article focuses on the extent to which the learning design was both implemented and working as intended and offers an examination of proximal outcomes and an initial examination of distal outcomes. The authors claim that the video-club's core activity – watching and discussing the video-excerpts – was successful in generating the requisite 'teacher talk' necessary to influence clinical educators' teaching practices. The examination of the video-clubs' impact on clinical educators' practice was promising and justifies a larger study to fully investigate the intervention's effectiveness. In order for the video-club to grow and thrive, systemic changes, particularly at the level of policy and 'culture', are likely to be required.